2007
DOI: 10.1111/j.1574-6968.2007.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological response of Arthrobacter protophormiae RKJ100 toward higher concentrations of o-nitrobenzoate and p-hydroxybenzoate

Abstract: Bioremediation of sites that are heavily contaminated with pollutant chemicals is a challenge as most of the microorganisms cannot tolerate higher concentrations of toxic compounds. Only a few strains of the genus Pseudomonas have been studied for their tolerance toward the higher concentrations of aromatic pollutant compounds, a phenomenon that is accompanied by various physiological changes. In the present study we have characterized the growth response and physiological changes (adaptations) of a Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…A comparative characterization of benzene-induced fatty acid composition showed that the benzene-sensitive strain was unable to increase the ratio of saturated : unsaturated fatty acid, while the tolerant strain showed significant changes in the saturated : unsaturated fatty acid within the cell membrane (Gutierrez et al, 2003). Similarly, Sharma et al (2007a) reported an overall increase in the ratio of trans : cis unsaturated fatty acid in the total cell fatty acid analysis of a benzoate-tolerant bacterial strain when it was subjected to extremely high concentrations of nitrobenzoate or hydroxybenzoate. The effective contribution of phospholipid composition towards tolerance of Pseudomonad was shown in a study wherein all the test Pseudomonad altered the phospholipid composition and relative concentrations in response to their growth in the presence of toluene (in comparison with those grown on sodium succinate) (Fang et al, 2000).…”
Section: Biotic Factorsmentioning
confidence: 84%
See 2 more Smart Citations
“…A comparative characterization of benzene-induced fatty acid composition showed that the benzene-sensitive strain was unable to increase the ratio of saturated : unsaturated fatty acid, while the tolerant strain showed significant changes in the saturated : unsaturated fatty acid within the cell membrane (Gutierrez et al, 2003). Similarly, Sharma et al (2007a) reported an overall increase in the ratio of trans : cis unsaturated fatty acid in the total cell fatty acid analysis of a benzoate-tolerant bacterial strain when it was subjected to extremely high concentrations of nitrobenzoate or hydroxybenzoate. The effective contribution of phospholipid composition towards tolerance of Pseudomonad was shown in a study wherein all the test Pseudomonad altered the phospholipid composition and relative concentrations in response to their growth in the presence of toluene (in comparison with those grown on sodium succinate) (Fang et al, 2000).…”
Section: Biotic Factorsmentioning
confidence: 84%
“…One of the most common stresses encountered during in situ bioremediation is the elevated concentrations of target pollutant and cross-contamination of other nontargeted pollutants (Lee & Lin, 2006). Quite often, the concentration of the pollutant(s) at the source of contamination is high enough to kill the majority of the microorganisms; consequently, the role of bacterial adaptations to a higher pollutant concentration becomes extremely significant for successful implementation of in situ bioremediation (van der Meer et al, 1992;van der Meer, 1994;Sikkema et al, 1995;Sharma et al, 2007a). Chemical pollutants (especially the organic compounds and solvents) are best-characterized microbial biocides, most of which affect the microbial cell survival by altering the biological membrane structure or by impairing the crucial biosynthetic pathways essential for the bacterial growth (Barrette et al, 1989;Sikkema et al, 1995;Bogdanov et al, 1999).…”
Section: Biotic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bordetella bronchiseptica infects mainly immune-suppressed populations of humans and causes respiratory tract related disease in dogs, cats and rabbits [50]. Arthrobacter protophormiae , when pre-exposed to lower concentration of ONB (O- nitrobenzoate) and PHB (p- hydroxybenzoate) will change its cellular fatty acid profile and adapt itself to survive in high concentration of ONB and PHB [51]. A. mysorens causes erythema characterized by localized skin infection [52].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from hydrophobicity measurement, the MATH test has also found uses in mixed culture analysis as a method to produce progressively hydrophobic strains as well as to separate out hydrophobic and hydrophilic strains [14,15]. This widely used technique finds applications in bioremediation [11,18,19], microbial adhesion and transport [20,21], microbially enhanced oil recovery (MEOR) [16,17], pathogenesis [10,[22][23][24], oral hygiene [9,25] and food contamination studies [26,27].…”
Section: Introductionmentioning
confidence: 99%